Pathogenetic aspects of treatment of patients with genital endometriosis and syndrome of chronic pelvic pain in combination with "proliferative genital syndrome". - Grek, L. (Medicni Perspektivi, 2018)
The aim of the work is to ascertain the efficiency of the use of an offered way of the complex treatment of the patients with genital endometriosis and combined benign pathologies of genitals and СРР. A differentiated approach to treatment and analysis of its effectiveness was conducted among the patients of the 1st and 2nd study groups (85 patients) with the severe and moderate pain syndrome according to the VAS scale. On the basis of analysis of immunohistochemical markers ER, PGR, Ki-67, VEGF, COX-2 inglands and in stroma the therapy was developed: Severe pain syndrome was eliminated in all patients within 3 months of treatment. A moderate level of pain was noted in 77.65%, after 12 months of observation in 16.47% of women, the remaining 83.53% noted a weak level of pain by VAS scale (p<0.05). The level of depression dropped (from 11,22±0,5 baseline to 5,98±0,24 ina year, p<0,001) by the Hamilton scale. This indicates the effectiveness of treatment.